Rhetorical moves in medical research article introductions: Alternative strategies adopted by English and German native speakers - Bennett, Deborah (2017)
Young doctoral students for whom English is an additional language are facing increasing pressure to publish their research in high-ranking English-language periodicals. However, a number of potential linguistic obstacles to editorial acceptance have been identified, including ‘interference’, a process in which specific rhetorical strategies adopted in the discourse of the home ‘large’ culture are transferred into the target language during the writing process. In this study, I investigate this phenomenon in my own teaching context by using rhetorical move analysis to explore the manner in which native speakers of English and German employ rhetorical strategies in introduction sections to original research articles in medicine. While a number of existing studies point towards differences in the rhetorical organisation of English and German academic writing, a critical examination of their work reveals some significant conceptual and methodological flaws. Chief among these are a deterministic, essentialist perception of culture and a lack of rigorous quantitative analysis. In an endeavour to address this, this study adopts an intercultural rhetoric theoretical framework to root the texts firmly in their socio-cultural context and utilizes a method combining quantitative corpus-analysis with qualitative text analysis, thus adopting both a top-down and a bottom-up approach. While the study reveals a broad congruence between the two cultures in terms of fundamental move structure, it also demonstrates the existence of significant differences in the ways in which German and US-American medical researchers employ specific rhetorical steps to reference other scholars’ contributions and to establish the necessity of their own research. These findings provide a basis for the development of pedagogical strategies to raise students’ awareness of the range of specific rhetorical steps at their disposal. Developing such an awareness will not only furnish them with a larger number of rhetorical resources to develop the richness of their writing, but will also facilitate more accommodative reading, sensitising them to a range of different author strategies.